DDIS-19. USING MATCHED PRIMARY AND RECURRENT PEDIATRIC BRAIN TUMOR ORTHOTOPIC MOUSE MODELS(PDOX) TO ILLUSTRATE THE GENETIC REVOLUTION AND TO INFORM NEW ANTI-RECURRENT PERSONALIZED THERAPIES. (11th November 2019) - Du, Yuchen; Kogiso, Mari; Braun, Frank; Qi, Lin; zhang, Huiyuan; Lindsay, Holly B; zhao, Sibo; Kool, Marcel; Stephan, Clifford; Li, Xiaonan
Abstract: BACKGROUND AND PURPOSE: Despite standard treatment largely benefits patients' survival, tumors may recur as aggressive, therapy resistant relapses. It is imperative to obtain a better understanding of molecular changes that occur after primary tumor resection and treatment. We established a serial of PDOX models using patient tumor tissues procured at different time of patient clinical history. METHODS: Dissociated tumor cells were cultured in vitro and transplanted into mouse brains. DNA and RNA were then extracted from tumor tissues or cells from patient and established xenografts. Whole genome methylation and transcriptomic profiling as well as histological phenotypes were examined. Standard therapies were conducted in xenografts. RESULTS: Currently, three sets of matched primary and recurrent tumor xenografts (19850PNET, 100815GGG/GBM and 5958MB) were established. Tumor-take rate increased from 50–70% of primary tumors to 100% of recurrent tumors with decreased tumor onset time (6 months to 3 months), which demonstrated progressive phenotypes. RNA sequencing reveals preserved and newly changed genetic changes in recurrent tumors. High-throughput drug screening discovered a shared and a diverse panel of therapeutic targets that could be selected further for in vivo drug treatment especially for recurrent tumors. Tumor xenografts responded to standard therapy either same or different from clinic outcome, which might indicate the intrinsic or inducible evolutional molecular changes during cancer progression and treatment at different stages. CONCLUSION: Three sets of matched primary and recurrent pediatric brain tumors, PNET/PNET, GGG/GBM and MB/MB, were successfully established in pediatric orthotopic mice tumor models (PDOXs) providing clinically-relevant and biologically-accurate animal model systems for development of novel therapeutic targets especially for recurrent tumors. Responses of primary and recurrent tumor xenografts to standard chemo-therapy were different possibly due to evolutionarily molecular changes in recurrent tumors during progression or induced by therapies.